SALCRA: ITS CONTRIBUTIONS TO THE SOCIO-ECONOMIC DEVELOPMENT OF SARAWAK RURAL AREAS - Dayangku Norasyikin, Awang Tejuddin; Karubi, Nwanesi Peter (Oil Palm Industry Economic Journal (OPIEJ), 2023)
Sarawak Land Consolidation and Rehabilitation Authority (SALCRA) are currently managing 19 oil palm estates for participants and five oil palm mills. These oil palm plantations and oil mills employ thousands of workers both professional and handymen/women. Our findings indicate that the oil palm industry has enhanced people’s economic well-being and has ensured that unutilized land is economically viable as a result of oil palm cultivation. At the same time, it is logical to argue that the oil palm plantations and oil mills have economically empowered many communities that are housing them directly and indirectly. Data from the field indicates that people around oil palm fields and those involved in the cultivation process show pictures of benevolent plants. Working within the premises of the Sarawak state government, SALCRA works to create a well-balanced urban and rural development based on a holistic development benefit for the people of Sarawak, regardless of their place of residence and work. The oil palm has different meanings depending on the informants involved. Furthermore, the SALCRA management team has continued to promote and implement a systematic development plan for Native Customary Rights land (NCR land) on a commercial basis.